Testing for Labor Market Equilibrium with an Exact Excess Demand Disequilibrium Model - Rudebusch, Glenn D. (The Review of Economics and Statistics, 1986)
A bstract-The standard disequilibrium model is supplemented with outside information on the extent of market excess demand. Estimation of this supplemented model is considerably less involved than that of the standard model, and certain desirable structural features, such as improved dynamics, are obtained. In addition, a simple nested test of the hypothesis of market equilibrium is available. The model is estimated with aggregate U.S. post-war labor market data, and the econometric test rejects the hypothesis of labor market equilibrium.